Up to Their Elbows in Blood: The Crimean War and the Professionalization of Medicine - Eaves, Tyler W. (Kansas State University. Dept. of History, 2017)
Fought in the mid-1850s, many scholars regard the Crimean War as largely insignificant. However in reality, the historical contributions of the war are important – particularly those contributions pertaining to medicine. This seemingly “unnecessary” war facilitated the modernization of Western medicine; methods used during and directly after the Crimean War were standard until World War Two. A brief history of the war reveals medical data that constitutes the bulk of my interpretation. The war’s specific medical achievements are highlighted throughout the essay. The findings in this paper are by no means conclusive, but they exhibit that it is important to look beyond Florence Nightingale, the war’s most famous and studied individual, and gaze upon the larger trends of medicine. Her story is covered in some detail in this paper, but she is not the sole source of innovation from this rather disastrous war. The professionalization of Western medicine stands out as one of the great accomplishments of this war, despite scholars viewing the war as useless.
Keywords: Cholera epidemics; Battlefield surgery; Medical modernization; Florence Nightingale; Nikolay Pirogov; William Howard Russell